2022
DOI: 10.1111/irv.13004
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of all‐cause mortality among patients hospitalized with influenza, respiratory syncytial virus, or SARS‐CoV‐2

Abstract: Background Shared and divergent predictors of clinical severity across respiratory viruses may support clinical and community responses in the context of a novel respiratory pathogen. Methods We conducted a retrospective cohort study to identify predictors of 30‐day all‐cause mortality following hospitalization with influenza ( N = 45,749; 2010‐09 to 2019‐05), respiratory syncytial virus (RSV; N = 24 345; 2010‐09 to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 52 publications
2
7
2
Order By: Relevance
“…2,20,24 In our dataset, however, comorbidity registered as CCI was not associated with mortality following hospitalisation with a respiratory virus infection. This may seem in contrast to other findings; [25][26][27] however, this in mortality rates following hospitalisation. 9,10,[28][29][30] In the initial phases of the pandemic, changes in admission decisions 31 and improved supportive care 9,32,33 are thought to have contributed most to the decline in mortality.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…2,20,24 In our dataset, however, comorbidity registered as CCI was not associated with mortality following hospitalisation with a respiratory virus infection. This may seem in contrast to other findings; [25][26][27] however, this in mortality rates following hospitalisation. 9,10,[28][29][30] In the initial phases of the pandemic, changes in admission decisions 31 and improved supportive care 9,32,33 are thought to have contributed most to the decline in mortality.…”
Section: Discussioncontrasting
confidence: 99%
“…In our dataset, however, comorbidity registered as CCI was not associated with mortality following hospitalisation with a respiratory virus infection. This may seem in contrast to other findings; 25–27 however, this discrepancy might in part be explained by a mitigating effect of influenza vaccination in high‐risk individuals, or by a lower admission threshold for those with expected severe progression of disease.…”
Section: Discussioncontrasting
confidence: 60%
“…The cumulative mortality rate over these three years is comparable to the annual mortality rate reported by other studies of RSV mortality in patients with comorbidities [ 19 ]. A study based on administrative data in Ontario, Canada, reported death rates among hospitalized patients (all ages) of 7.0% for influenza and 2.9% for RSV [ 20 ]. However, data from this paper demonstrated higher mortality when limited to only adults aged 20+ (8.2% for influenza and 10.1% for RSV) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another systematic review and meta-analysis found that the in-hospital case fatality rate was higher in adults 65 years of age and older than adults 50 to 64 years of age (1). Similarly, two studies from Ontario found that among patients hospitalized with RSV, 30-day all-cause mortality rates increased with increasing age (12,17). A US prospective cohort study found that the CFR was higher in adults admitted from LTC facilities (38%) than in those admitted from the community (3%, p<0.001) (18).…”
Section: Death Associated With Rsv Infectionmentioning
confidence: 99%